2017
DOI: 10.21608/jappmu.2017.46013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Iodine Supplementation on Productive Performance of Pekin and Domyati Ducks during Growth Period

Abstract: A total number of Two hundred and forty , day old unsexed Pekin and Domyati ducklings (120/each breeds) at one-day old were used in the present study. The experimental period extended for 12 weeks of age. Experimental ducks were randomly divided into four equal treatments (30 Pekin or Domyati ducks each) in three equal replicates (10 ducks each). Ducks were fed diets containing Potassium iodide at levels of 0, 1, 1.5 and 2 mg iodine/kg ration for T1, T2, T3 and T4, respectively. The results showed that growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
5
1
1
Order By: Relevance
“…These results may be due to the effect of KI on thyroid gland activity and the increase in thyroxine effects. Moreover, our results agree with Ali et al, (2017) who reported that the Hb and PCV% increase by adding iodine to the ration.…”
Section: ‫الــرافـديــن‬ ‫زراعـــة‬ ‫مـجـلـــة‬supporting
confidence: 93%
See 2 more Smart Citations
“…These results may be due to the effect of KI on thyroid gland activity and the increase in thyroxine effects. Moreover, our results agree with Ali et al, (2017) who reported that the Hb and PCV% increase by adding iodine to the ration.…”
Section: ‫الــرافـديــن‬ ‫زراعـــة‬ ‫مـجـلـــة‬supporting
confidence: 93%
“…Data of Table 3 showed a significant elevation in the lymphocyte %, and on the contrary, the heterophils % and H/L ratio significantly decreased with KI injection. These results corresponded with the findings of Ali et al, (2017), and with the findings of Abaza et al, (2003) who record a positive correlation between thyroxine levels and lymphocytes%.…”
Section: ‫الــرافـديــن‬ ‫زراعـــة‬ ‫مـجـلـــة‬supporting
confidence: 92%
See 1 more Smart Citation
“…Also, Awad et al (2016) reported that the improvement of eviscerated carcass and edible parts reached from 3.54 to 4.57% and 3.94 to 4.47%, respectively, for Domyati ducklings fed the diet supplemented with different LC levels (150, 300, 450 and 600 mg/kg diet) as compared to control, while the abdominal fat percentage was decreased by 36.14 to 45.18%. Ali et al (2017) confirmed that carcass and total edible parts percentages were significantly increased due to duckling breed by 3.35 and 4.00% for Pekin ducklings than Domyati, respectively. El-Kelawy (2019) reported that Cr supplementation improved the percentage of carcass weight and decreased abdominal fat at 49 days of the age of Japanese quails compared with control groups.…”
Section: Carcass Traitssupporting
confidence: 60%
“…These results agreed with Ali (2005) who indicated that the mortality percentage was 4% for Domyati during the periods (0-12) weeks of age. Also, Ali et al (2017) reported that the mortality rate during 12 weeks of age was significantly higher in Pekin (4.79%) than Domyati (3.07%). Duckling dietary supplemented with different LC and Cr levels significantly recorded a reduction in mortality rate than those fed on control ration from 4.07 to 3.93%.…”
Section: Mortality Ratementioning
confidence: 97%